2008
DOI: 10.1038/nm1731
|View full text |Cite
|
Sign up to set email alerts
|

The Notch pathway in podocytes plays a role in the development of glomerular disease

Abstract: Albuminuria associated with sclerosis of the glomerulus leads to a progressive decline in renal function affecting millions of people. Here we report that activation of the Notch pathway, which is critical in glomerular patterning, contributes to the development of glomerular disease. Expression of the intracellular domain of Notch1 (ICN1) was increased in glomerular epithelial cells in diabetic nephropathy and in focal segmental glomerulosclerosis. Conditional re-expression of ICN1 in vivo exclusively in podo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
407
2
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 367 publications
(445 citation statements)
references
References 45 publications
17
407
2
3
Order By: Relevance
“…1a). A previous report showed Notch activation in a diabetic mouse model and in puromycin aminonucleoside (PAN)-treated rats 14 . First, we examined the Notch activation in mice with ADR nephropathy.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1a). A previous report showed Notch activation in a diabetic mouse model and in puromycin aminonucleoside (PAN)-treated rats 14 . First, we examined the Notch activation in mice with ADR nephropathy.…”
Section: Resultsmentioning
confidence: 99%
“…The functions of Notch pathway in glomerular diseases remain mostly unclear. So far, two reports evaluated the blockade of Notch pathway using GSI in a rodent model of nephrotic syndrome or genetic engineering in mice 14,27 . Interestingly, they demonstrated the opposite results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was driven by a Notch-mediated downregulation of the cell cycle inhibitors p21 and p27, which forces progression toward mitosis of a cell that cannot assemble an efficient mitotic spindle, because it poorly expresses Aurora kinase B [75]. Interestingly, Notch expression is virtually absent in glomeruli of healthy adult kidneys, while several studies demonstrated strong Notch upregulation in podocytes of patients affected by several types of glomerular disorders characterized by podocyte death [75, 77, 78]. In addition, persistent activation of Notch in podocytes leads to podocyte loss and FSGS [75].…”
Section: The Podocyte’s Catastrophe: Lost Cell Cycle Controlmentioning
confidence: 99%
“…Indeed, the inappropriate activity of developmental pathways can be causative of renal disease. Niranjan et al [13] report that over-activity of the Notch pathway in podocytes can lead to apoptosis and resultant proteinuria, while genetic or biochemical suppression of this pathway, which is known to be critical for normal proximal tubular development [14,15], prevents glomerulosclerosis and proteinuria.…”
Section: Renal Repair Recapitulating Development: Yes or No?mentioning
confidence: 99%